Zinc-mediated binding of a low-molecular-weight stabilizer of the host anti-viral factor apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3G. Issue 18 (15th September 2016) - Radwan, Mohamed O.; Sonoda, Sachiko; Ejima, Tomohiko; Tanaka, Ayumi; Koga, Ryoko; Okamoto, Yoshinari; Fujita, Mikako; Otsuka, Masami
Graphical abstract: Abnormal ubiquitination leads to inhibition of proteasome degradation of A3G, suppressing reverse transcription of HIV-1 deaminase-independently in a target cell. Abstract: Apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3G (APOBEC3G, A3G), is a human anti-virus restriction protein which works deaminase-dependently and -independently. A3G is known to be ubiquitinated by HIV-1 viral infectivity factor (Vif) protein, leading to proteasomal degradation. A3G contains two zinc ions at the N-terminal domain and the C-terminal domain. Four lysine residues, K 297, K 301, K 303, and K 334, are known to be required for Vif-mediated A3G ubiquitination and degradation. Previously, we reported compound SN-1, a zinc chelator that increases steady-state expression level of A3G in the presence of Vif. In this study, we prepared Biotin-SN-1, a biotinylated derivative of SN-1, to study the SN-1–A3G interaction. A pull-down assay revealed that Biotin-SN-1 bound A3G. A zinc-abstraction experiment indicated that SN-1 binds to the zinc site of A3G. We carried out a SN-1–A3G docking study using molecular operating environment. The calculations revealed that SN-1 binds to the C-terminal domain through Zn 2+, H 216, P 247, C 288, and Y 315 . Notably, SN-1-binding covers the H 257, E 259, C 288, and C 291 residues that participate in zinc-mediated deamination, and the ubiquitination regions of A3G. The binding of SN-1 presumably perturbs the secondary structure between C 288 and Y 315, leading to less efficient ubiquitination.